Pelatihan Pengolahan Cangkang Tiram Secara Tradisional Bagi Ibu-Ibu Petani Tiram di Desa Alue Naga Syiah Kuala Banda Aceh - Lia handayani; Azwar Thaib; Nurhayati nurhayati; faisal syahputra; Dwi Apriliani; Suraiya Nazlia; Ainal mardhiah (Universitas Lancang Kuning, 2022)
The majority of people work as fishermen and their geographical location on the coast make Gampong Alue Naga produce quite a lot of fishery waste, especially oyster shells. Its use will have many good impacts on people's lives because in addition to reducing waste that interferes with the environment, the use of oyster shells can also reduce costs for animal feed and provide additional income for families. The target of this activity is fishermen housewives who generally also work as oyster seekers, so that they have no trouble finding raw materials and the waste they produce can be used immediately. The results of this activity are considered very satisfactory because the participants of the activity can understand the process of processing oyster shells, understand the use of the grit flour produced and directly utilize the grit flour product as animal feed.